SAND FRACTION ESTIMATION IN THE TOPSOIL OF THE PANTANAL BIOME: A PRELIMINARY APPROACH USING EMISSIVITY DATA - Breunig, Fábio Marcelo; Nascimento, Edenilson Roberto; Sampaio, Tony Vinicius Moreira; Berra, Elias Fernando; Frick, Elaine de Cacia de Lima; Adami, Marcos; Galvão, Lênio Soares; Trentin, Romário; Gaida, William; Santos, Leonardo José Cordeiro; et al. (Ra’e Ga: o Espaço Geográfico em Análise, 2025)
The Pantanal Biome is characterized by its high biodiversity of fauna and flora, largely associated with its floodplain. With the increasing occurrence of extreme events such as droughts, floods, and fires, the risks of environmental degradation and the intensification of processes like the increase of sand in the floodplain (sandization) also rise. This study aims to estimate the sand fraction in the surface horizons of the soils in the Pantanal Biome using thermal infrared data. These estimates were obtained from the emissivity data of the Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) Global Emissivity Dataset (GED). In addition to emissivity data, elevation and hydrography data were also considered. To estimate the sand fraction, an empirical regression model was employed. Spectral analysis of sandy terrains revealed features associated with the presence of silica (Reststrahlen features), enabling its distinction from green/dry vegetation and water. Normalization of thermal band data allowed the application of a logistic model to estimate the distribution of areas with higher concentrations of sand fraction in the Pantanal soils. The eastern, central, and central southern sections have higher concentrations of the sand fraction. The results suggest a partial a relationship between the sand percentage, small altimetry variations in the biome, and the absence of permanent drainage systems. Further studies should be conducted to validate the model, and caution is recommended when interpreting and using the results presented.